Needlestick injury in a pregnant inpatient in an overcrowded hospital - Nnabuike Chibuoke Ngene; Chioma Obiageli Onyia; Jagidesa Moodley; Mokete Joseph Titus (AOSIS, 2014)
Needlestick injury (NSI) is commonly reported among healthcare workers, but is not well documented in patients. We report a case of an NSI in an HIV-negative, gestational hypertensive patient admitted to a hospital for induction of labour at term. Owing to an insufficient number of hospital beds, patients were seated in an overcrowded corridor of the antenatal ward where a patient stepped on the needle of an inadvertently disconnected intravenous infusion set of another pregnant patient, who was HIV-infected. The injury occurred prior to labour induction. Antiretroviral post-exposure prophylaxis to prevent HIV infection was administered to the injured patient and her newborn. This report illustrates how hospital bed shortage may compromise patient safety and discusses measures to prevent NSI among patients and hospital overcrowding.